PHILIPPINE CATHOLICISM AND SECULARIZATION: FACE-OFF, DENIAL OR DIALOGUE? - Abellanosa, Rhoderick John S. (Asian Horizons, 2013)
When the Second Vatican Council says in Lumen Gentium that it focuses its attention on the world of men [and women], calling it as the theatre of human history, an ecclesiological shift happened. The distinction between the Church “and” the world was reinterpreted in favour of a Church “in” the world.1 Thus, the world which the Council Fathers call the theatre of humanity is practically the Church’s own theatre. The Church is not totally different from the world because it is in the world. It is not a perfect society that ontologically exists outside of the world’s premises but rather one that engages the various states and institutions within the same sphere.